Tingkat Partisipasi Angkatan Kerja Menurut Jenis Kelamin - Muhammad Abdullah Tawakal; Marthen A.I Nahumury (Faculty Of Economics and Business, Musamus University, 2020)
This study aims to determine the level of labor force participation in Merauke Regency by gender. The type of data in this study is data obtained from the statistical center of Merauke district with the period of 2017-2018. The method used in this study is the method of data processing using coding or data (coding) and editing. While the analysis of labor force participation rates uses the formula of labor force participation rate (TPAK). The results of this study were obtained, the level of labor force participation by sex in Merauke Regency was dominated by male workers, where the rate of male labor force participation in 2017 was 81.69%, while for women it was 43.92%. Whereas for 2018 TPAK for men was 82.53% and for Women was 55.48%. Keywords: Participation in Work Force